ANALISIS RISIKO KECELAKAAN KERJA CV. BRENS BAKERY MENGGUNAKAN METODE HIRARC (HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL) - Prayoga, Dimas; Zuki, Meizul; Hidayat, Lukman (Jurnal Agroindustri, 2023)
CV. Brens Bakery is a Micro, Small and Medium Enterprises (MSME) engaged in the production of bread that provides various kinds of cakes, sponge with various variations, bread, donuts, and pastries. The problems that exist in the bread-making industry in the production section are the discovery of potential hazards that can cause a work accident at any time. Potential hazards such as butter splattered on the floor makes the floor slippery, noise from the use of machines that have the potential to disrupt the concentration of workers, the use of sharp equipment has the potential to injure hands, and the hot temperature near the grill has the potential to make workers easily experience fatigue when working. This study aims to determine the risk of work accidents, determine the level of risk of work accidents, and provide proposals for controlling the risk of work accidents that can occur in the bread making industry. The HIRARC (Hazard Identification Risk Assessment and Risk Control) method was used to analyze the risk of occupational accidents in this study by determining the type of work activity first which identified the cause of the hazard, to obtain the risk, then conducting risk assessment and control to prevent and reduce exposure to hazards that exist in each type of work. The results of the study obtained 30 risks which were categorized as 43% low risk, 37% medium risk, and 20% high risk and there were 30 risks control proposals consisting of 1 substitution, 7 design, 12 administrations, and 10 using PPE (Personal Protective Equipment).